COMPARATIVE EFFECTIVENESS OF SEFT AND PMR ON SLEEP QUALITY AMONG PRE-ELDERLY PATIENTS WITH HYPERTENSION - Sofiani; Yofa Anggriani Utama; Aris Citra Wisuda; Citra Suraya; Raden Surahmat; Risdayanti Raharjeng (Journal Of Nursing Science Research, 2026)
Hypertension remains one of the major global public health problems and is frequently associated with sleep disturbances that negatively affect quality of life and cardiovascular health. Poor sleep quality among hypertensive patients is closely related to increased sympathetic nervous system activity, psychological stress, and impaired physiological relaxation mechanisms. Non-pharmacological interventions such as Spiritual Emotional Freedom Technique (SEFT) and Progressive Muscle Relaxation (PMR) have increasingly been used to improve relaxation and sleep quality among patients with hypertension. This study aimed to analyze the comparative effectiveness of SEFT and PMR interventions on sleep quality among pre-elderly patients with hypertension at Makarti Mulya Primary Health Center, Ogan Komering Ilir. This study employed a quasi-experimental design using a pretest–posttest two-group approach. A total of 56 respondents were selected using purposive sampling and divided into the SEFT group (n=28) and PMR group (n=28). Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after intervention. Data were analyzed using Wilcoxon and Mann–Whitney tests with a significance level of p<0.05. The results demonstrated significant improvements in sleep quality in both groups. In the PMR group, good sleep quality increased from 35.7% to 71.4% (p=0.002), while in the SEFT group it increased from 25% to 78.6% (p=0.000). Mann–Whitney analysis showed no significant difference in effectiveness between SEFT and PMR interventions (p=0.541). In conclusion, both SEFT and PMR effectively improved sleep quality among pre-elderly patients with hypertension safely and non-pharmacologically